The Roles of Extension Workers In The Development of Farmer Group Karya Bakti Sakti: Peran Penyuluhan Pertanian Lapangan (PPL) Dalam Pengembangan Gabungan Kelompok Tani (GAPOKTAN) Karya Bakti Sakti - Zahra Rusydah Muthiah Naura Rusydah Salimah (Universitas Widya Gama Mahakam, 2023)
The research was to analyze the effect of the role of extension workers (facilitator, innovator, motivator and educator) toward the development of Gapoktan Karya Bakti Sakti. The research location was in Terusan Nunyai District, Central Lampung Regency. The research method used was purposive with simple random sampling with 66 members of Gapoktan Karya Bakti Sakti as samples. The analytical method used was descriptive analysis and multiple linear regression analysis. Research shows that the level of development of Gapoktan Karya Bakti Sakti was in level moderate (53%). Facilitator, innovator, and educator variables significantly influence toward development of Gapoktan Karya Bakti Sakti. The motivator variable had no effect on the development of Gapoktan Karya Bakti Sakti. Based on the research results, the role of extension workers can be developed by identifying to improve product value. Keywords: cassava, development, farmer groups, the role.